The mediating role of phubbing in the relationship between self-efficacy and problematic Instagram use - Tuğçe Peker Akman; Emrah Akman; Şenel Çitak (BMC Psychology)
Abstract This study explores the mediating role of phubbing behaviour in the relationship between university students’ self-efficacy and problematic Instagram use. Utilizing a quantitative relational design, Structural Equation Modeling (SEM) was employed to analyse the relationships among the variables. The findings reveal an association where higher self-efficacy is related to lower problematic Instagram use. This relationship appears to be mediated by phubbing behaviours, with higher self-efficacy also being associated with lower phubbing. Higher self-efficacy was associated with lower phubbing tendencies and lower reported problematic Instagram use. The study underscores the importance of addressing both psychological traits, such as self-efficacy, and behavioural factors, like phubbing, in developing interventions to address problematic social media use. Recommendations include implementing self-efficacy enhancement programs and raising awareness of the detrimental associations of phubbing on university campuses. These results contribute to a deeper understanding of the interplay between psychological and behavioural factors in problematic social media use and offer potential considerations for prevention efforts.